+0

# find using first principles the derivative of cosx

0
281
3

find using first principles the derivative of cosx

Guest Nov 26, 2014

#1
+26544
+10

.

Alan  Nov 26, 2014
Sort:

#1
+26544
+10

.

Alan  Nov 26, 2014
#2
+91900
+5

$$\\\displaystyle \lim_{h\rightarrow 0}\;\;\;\frac{f(x+h)-(x)}{h}\\\\ =\displaystyle \lim_{h\rightarrow 0}\;\;\;\frac{cos(x+h)-cos(x)}{h}\\\\ =\displaystyle \lim_{h\rightarrow 0}\;\;\;\frac{cosx*cosh-sinx*sinh-cos(x)}{h}\\\\ =\displaystyle \lim_{h\rightarrow 0}\;\;\;\frac{cosx(cosh-1)-sinx*sinh}{h}\\\\ =\displaystyle \lim_{h\rightarrow 0}\;\;\;\frac{cosx(cosh-1)}{h}-\frac{sinx*sinh}{h}\\\\ =\displaystyle \lim_{h\rightarrow 0}\;\;\;cosx*\frac{(cosh-1)}{h}-sinx*\frac{sinh}{h}\\\\ =cosx*0-sinx*1\\\\ =0-sin(x)\\\\ =-sin(x)$$

If you need these proved that also be done

$$\\\displaystyle \lim_{h\rightarrow 0}\;\;\;\frac{cosh-1}{h}=0\\\\ \displaystyle \lim_{h\rightarrow 0}\;\;\;\frac{sinh}{h}=1\\\\$$

Melody  Nov 26, 2014
#3
+19054
+5

find using first principles the derivative of cosx

$$\boxed{ e^{i\phi}= \cos{(\phi)}+i\sin{(\phi)} }$$

$$e^{i\phi}= \cos{(\phi)}+i\sin{(\phi)} \quad | \quad \frac {d}{dx}$$

$$\left( e^{i\phi} \right)' = ie^{i\phi} = \left( \cos{(\phi)}+i\sin{(\phi)} \right) ' = (\cos{(\phi)})'+i(\sin{(\phi)})'$$

$$ie^{i\phi} = (\cos{(\phi)})'+i(\sin{(\phi)})' \\ i\left( \cos{(\phi)}+i\sin{(\phi)} \right) = (\cos{(\phi)})'+i(\sin{(\phi)})' \\ i\cos{(\phi)}+\underbrace{i^2}_{i^2=-1}\sin{(\phi)} = (\cos{(\phi)})'+i(\sin{(\phi)})' \\ i\cos{(\phi)}-\sin{(\phi)} = (\cos{(\phi)})'+i(\sin{(\phi)})' \\ { -\sin{(\phi)} } + i{\cos{(\phi)} }= { (\cos{(\phi)})'}+i {(\sin{(\phi)})'}\\ \\ {\boxed{ (\cos{(\phi)})'= -\sin{(\phi)} }} \\ {\boxed{ (\sin{(\phi)})'= \cos{(\phi)} }} \\$$

heureka  Nov 26, 2014

### 7 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details